Inequalities in healthy life expectancy by Federated States - Szwarcwald,Célia Landmann (2017)
ABSTRACT OBJECTIVES To estimate the healthy life expectancy at 60 years by sex and Federated States and to investigate geographical inequalities by socioeconomic status. METHODS Healthy life expectancy was estimated by the Sullivan method, based on the information of the National Survey on Health, 2013. Three criteria were adopted for the definition of “unhealthy state”: self-assessment of bad health, functionality for performing the activities of daily living, and the presence of noncommunicable disease with intense degree of limitation. The indicator of socioeconomic status was built based on the number of goods at household and educational level of the head of household. To analyze the geographical inequalities and socioeconomic level, inequality measures were calculated, such as the ratio, the difference, and the angular coefficient. RESULTS Healthy life expectancy among men ranged from 13.8 (Alagoas) to 20.9 (Espírito Santo) for the self-assessment criterion of bad health. Among women, the corresponding estimates were always higher and ranged from 14.9 (Maranhão) to 22.2 (São Paulo). As to the ratio of inequality by Federated State, the medians were always higher for healthy life expectancy than for life expectancy, regardless of the definition adopted for healthy state. Regarding the differences per Federated State, the healthy life expectancy was seven years higher in one state than in another. By socioeconomic status, differences of three and four years were found, approximately, between the last and first fifth, for men and women, respectively. CONCLUSIONS Despite the association of the mortality indicators with living conditions, the inequalities are even more pronounced when the welfare and the limitations in usual activities are considered, showing the necessity to promote actions and programs to reduce the socio-spatial gradient.